Intra-national Ethnic Diasporas: Popular Culture and Mediated Translocal Spaces in Kenya - Ogone, James Odhiambo (My University, 2015)
Diasporas are conventionally perceived in terms of dispersed populations on a transnational scale. However, this paper demonstrates that the international dimensions of diasporas do not discount their potential for manifestation at intra-national levels, especially within countries made up of various distinct ethnic ‘nations’. In the multiethnic African context, populations tend to construct an ‘imagined community’, within which connections are maintained among members scattered beyond the boundaries of the homeland, but still within the confines of the nation in question. In this paper, attention is paid to the dynamics involved in the local ethnic populations’ appropriation of communication technologies to render mediated popular culture and construct translocal spaces in Kenya. It emerges that through vernacular radio, television, and mobile phones, the in-country diasporas maintain vital socio-cultural contact among members. By mainstreaming local migrants, whose experiences remain hardly visible in contemporary scholarly discourse, this paper accordingly expands the definition of diaspora.